Uji Organoleptik dan Umur Simpan Soyghurt dengan Berbagai Konsentrasi Gula dan Waktu Inkubasi - Firsty Vanezza Gabriela; Frista Chairunnisa; Nadhifah Raniah; Rama Pratama; Monica Kharisma Swandi; Nur Azizah (Department of Biology, Faculty of Agriculture, Fisheries and Biology, University of Bangka Belitung, 2021)
One of fermented soybean (Glycine max L. Merr) products is soy milk, called as Thew Fu Sui by the community of Bangka Belitung. Soy milk product has unpleasant aroma or “langu” and need to be processed into alternative product such as yogurt. Soy milk yogurt (soyghurt) was made by utilizing the same bacteria in yogurt-making from animal milk including Streptococcus thermophillus and Lactobacillus bulgaricus. Sugar concentration and incubation time were the factors that influenced the fermentation process and product’s taste. This research was conducted to determine the level of people's preference for soyghurt by organoleptic assessment of color, taste, aroma and texture based on variation of sugar concentration and incubation time of soyghurt. Our study found that various additional sugar concentration and incubation time gave difference result in organoleptic test. Soyghurt with 10%, 12.5%, and 15% of sugar addition became more favorable among the participant. The incubation time of 8 hours, 12 hours, and 16 hours equally produced good fermentation results. Storage in refrigerator for 1 days could maintain its flavor, texture, colour and aroma, but changed after 2 days stored.